PERBANDINGAN KARAKTERISTIK KOLAGEN KULIT IKAN GABUS, MAS DAN LELE - Sulthoniyah, Siti Tsaniyatul Miratis; Hasanah, Finatun; Adharani, Nadya (Program Studi Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas PGRI Banyuwangi, Jalan Ikan Tongkol No 01, Telp (0333) 421593, 428592 Banyuwangi 68416, 2025)
Collagen is one of the proteins in animal, comprising approximately 30% of the total protein content in animals. It is commonly found in muscles, skin, and scales of animals. This study utilized three types of freshwater fish, namely snakehead fish, common carp, and catfish. Aim of the research was to compare the characteristics of skin collagen from snakehead fish, common carp, and catfish. The research method was an experimental design involving treatments on three different fish species with four replications. The parameters tested included yield, protein content, and moisture content. The results indicated that the highest yield was obtained from catfish skin collagen at 15.7%. The highest protein content was found at common carp skin collagen, while the best moisture content was observed from snakehead fish skin collagen.